Polarization-driven thermal emission regulator based on self-aligned GST nanocolumns - Joo Hwan Ko; Do Hyeon Kim; Sung-Hoon Hong; Sun-Kyung Kim; Young Min Song (iScience, 2023)
Summary: The increasing advances in thermal radiation regulators have attracted growing interest, particularly in infrared sources, thermal management, and camouflage. Despite many advances in dynamic thermal emitters with great controllability, sustained external energy is required to maintain the desired emission. In this study, we present a polarization-driven thermal emission regulator based on a two-way control: i) phase change and ii) polarization tuning. Based on a conventional, non-volatile phase change material, i.e., Ge2Sb2Te5 (GST), we newly introduce an anisotropic medium for facile emissivity regulation without heat energy consumption. A rigorous coupled-wave analysis method provides design guidelines for finding optimal structural parameters. We utilized a simple glancing angle deposition process which induces tilted self-aligned nanocolumns with anisotropic properties. The fabricated sample shows polarization-sensitive thermal regulation through thermal imaging spectroscopic measurement. Additionally, we manufactured a multispectral visibly/thermally camouflaged patch that identifies encrypted information at a specific polarization state for a proof-of-concept demonstration.